Assessing Field Degradation of Photovoltaic Modules by Near-Infrared Absorption Spectroscopy of Ethylene Vinyl Acetate Encapsulant - Stroyuk, Oleksandr; Buerhop, Claudia; Wittman, Ernst; Mashkov, Oleksandr; Stephan, Pascal; Crozier McCleland, Jacqui; Vumbugwa, Monphias; Vorster, Frederik; van Dyk, Ernest; Hauch, Jens; Brabec, Christoph; Peters, Marius (Solar RRL, 2024)
The degradation status of polymer encapsulants in photovoltaic (PV) modules with backsheets of various compositions is evaluated by near-infrared absorption (NIRA) spectroscopy. The method is used to identify backsheet types and to assess the content of carbonyl species in the ethylene vinyl acetate copolymer encapsulant expressed as a carbonyl index (CI). The CI distributions are collected for PV modules of different ages and in different climatic conditions from twelve PV installations in Europe (EU) and South Africa (ZA) and the peak of the index distribution is found to be related exponentially to the total dose of solar irradiation. The CI growth rate with the irradiation dose in EU is around two times larger than in ZA, most probably due to more massive moisture ingress into PV modules installed in a more humid EU climate. For similar total solar exposures, the CI is found to depend on the backsheet structure. Repeated measurements on the same plant after an additional 2 years of module operation confirm the capacity of NIRA spectroscopy to track the temporal progression of encapsulant degradation using CI as a quantifier depending on the encapsulant-backsheet bill of materials, plant age, and climatic zone.
CRIS-Team Scopus Importer:2024-03-15
Keywords: backsheets; bill-of-materials; encapsulants; near-infrared spectroscopy